A survey of family therapists’ adult attachment styles in the United Kingdom - Yusof, Yusmarhaini; Carpenter, John S. W. (Springer International Publishing, 2013)
Research on individual therapy suggests that the ability to build effective therapeutic alliances with clients is related to the therapist’s adult attachment style.This paper reports an on-line survey of the attachment styles of registered family therapists in the UK which investigated associations between therapist’s attachment style, prior profession, gender and preference for a model of therapy.All 443 UK registered family therapists were surveyed and 82 (19 percent) replied.The survey included two standardised self-report measures: the Relationship Questionnaire (RQ) (Bartholomew and Horowitz in Pers Soc Psychol 61:226–244, 1991) and the Experiences in Close Relationships Questionnaire (ECR) (Brennan et al. in Attachment theory and close relationship. The Guilford Press, New York, 1998).The RQ invites respondents to rate the extent to which descriptions of secure, preoccupied, dismissing and fearful attachment styles applied to themselves.The ECR is a more conventional measure similar to a personality inventory. Responses to the two measures were discrepant. On the RQ 61 self-reported as having a ‘secure’ attachment style, nine ‘preoccupied’, six ‘dismissing’ and six were ‘fearful’. Responses to the ECR indicated that 24 were ‘secure’, 16 ‘preoccupied’, 15 ‘dismissing’ and 27 ‘fearful’.Attachment style, as measured by the ECR, was not associated with therapists’ prior profession, gender and preference for a model of therapy.The discrepancy between measures may be attributable to the more transparent RQ measure.Participants’ responses may have been based on how they wanted others to view them or how they viewed themselves.These responses are challenged by the findings from the ECR which revealed apparently less desirable adult attachment styles in this sample.